THE ROLE OF ITK-SNAP SOFTWARE IN THE DIAGNOSIS AND MONITORING OF HEALING AFTER APICOECTOMY (Tạp chí Y học Cộng đồng, 2026)
Objective: To evaluate the role of ITK-SNAP software in the diagnosis and monitoring of healing after apicoectomy.Methods: A descriptive case series was conducted on 30 patients with 41 teeth and 36 lesions undergoing apicoectomy at the Institute of Odonto-Stomatology, Hanoi Medical University, from August 2020 to July 2021. Cone-beam computed tomography (CBCT) scans were obtained preoperatively, immediately postoperatively, and at 6 months. Preoperative lesion volumes were segmented and quantified using ITK-SNAP and subsequently categorized using a threshold of 247 mm³. In cases with 6-month follow-up CBCT, postoperative bone defect volumes were also measured immediately after surgery and at 6 months to assess bone regeneration. Healing was evaluated clinically at 1 week and 3 months. Radiographic healing was assessed at 6 months using the PENN 3D criteria.Results: The mean age of the patients was 34.37 ± 14.55 years, and 56.7% were male. Maxillary teeth accounted for 70.7% of cases. Periapical cysts represented 30.6% (11/36) of the lesions. Of lesions with a preoperative volume above 247 mm³, 76.9% were diagnosed as periapical cysts. In contrast, only 4.3% of lesions with a volume up to 247 mm³ were cystic (p
Keywords: ITK-SNAP; cone-beam computed tomography; periapical cyst; apicoectomy; three-dimensional segmentation; lesion volume.